2009
DOI: 10.1007/s10916-009-9381-7
|View full text |Cite
|
Sign up to set email alerts
|

Singular Spectrum Analysis of Sleep EEG in Insomnia

Abstract: In the present study, the Singular Spectrum Analysis (SSA) is applied to sleep EEG segments collected from healthy volunteers and patients diagnosed by either psycho physiological insomnia or paradoxical insomnia. Then, the resulting singular spectra computed for both C3 and C4 recordings are assigned as the features to the Artificial Neural Network (ANN) architectures for EEG classification in diagnose. In tests, singular spectrum of particular sleep stages such as awake, REM, stage1 and stage2, are considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…Use the first 2 3 rd observations to construct many different training sets, each one containing one more observation than the previous one. Apply the remaining 1 3 rd of observations to build corresponding test sets, each one containing one fewer observation than the previous one (see Figure 1).…”
Section: The Time Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Use the first 2 3 rd observations to construct many different training sets, each one containing one more observation than the previous one. Apply the remaining 1 3 rd of observations to build corresponding test sets, each one containing one fewer observation than the previous one (see Figure 1).…”
Section: The Time Seriesmentioning
confidence: 99%
“…As a result, there are continuous attempts at developing the underlying theory of SSA and improving its forecasting methods. Whilst the review of all applications of SSA are beyond the scope of this paper, those interested are referred to [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Nowadays, there is a bulk of research on SSA to develop its theory and applications and few such examples can be found in [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The remarkable features of SSA are that neither a parametric model nor stationarity-type conditions have to be assumed for the time series [1]. The SSA method is attracting considerable interest due to its widespread capabilities and it has many applications in a variety of fields such as medicine [2][3][4][5], biology and genetics [6,7], finance and economics [8][9][10][11][12][13][14][15][16], engineering [17][18][19][20][21][22][23], and other fields [24][25][26]. Whole and precise details on the theory and applications of SSA can be found in [1,[27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The Singular Spectrum Analysis (SSA) technique is a nonparametric time series analysis and forecasting technique which is transforming into an increasingly popular method for noise reduction and forecasting. Whilst it is not the objective of this paper to review all applications of SSA, we cite few of the recent articles as evidence of the increasing popularity of SSA (see for example, [1][2][3][4][5][6][7][8][9][10][11][12][13][14]). In brief, the SSA technique seeks to decompose a time series to identify the trend, signal, harmonic components and noise, and thereafter reconstructs a new, filtered time series which can be used for forecasting future data points [15].…”
Section: Introductionmentioning
confidence: 99%